Comparative Financial Analysis of Lowe’s and Home Depot for Investment Decisions - Zhao, Xiaoya (Simen Owen Academic Proceedings Series, 2025)
With nearly eighty years of presence in the U.S. home-improvement market, Lowe’s has enhanced asset efficiency and profitability through the advancement of digital tools, the expansion of professional-contractor services, and the refinement of supply-chain logistics. Compared to Home Depot, Lowe’s operates on a smaller scale yet achieves higher gross profit relative to assets, faster earnings-per-share growth, and a notably lower price-to-earnings-growth ratio, reflecting either an undervalued investment opportunity or market skepticism regarding the sustainability of its growth, which contributes to the observed discount in its price-to-earnings multiple. Brand equity remains strong, profit margins are stable, and the product assortment is increasingly concentrated in higher-margin categories such as smart-home devices and seasonal offerings. Challenges include softening consumer demand driven by rising interest rates, intensifying online competition led by e-commerce giants, and ongoing volatility in raw-material costs encompassing lumber, metals, and chemicals. In response, management is deepening engagement with professional customers, accelerating omnichannel investments that integrate physical stores with rapid delivery and buy-online-pick-up-in-store services, and diversifying the supplier base to reduce geographic and logistical concentration. Despite operating in a mature industry, the combination of operational leverage, strategic initiatives, and disciplined capital allocation suggests that Lowe’s retains substantial growth potential and sustained competitive resilience in the years ahead.